On demand services App following clean architecture - Habib, Salah Mounir; Goudjal, Youcef; Ben Saad, Mohamed Lahcen (Université Amar Telidji - Laghouat - Département d'informatique, 2022)
The demand for goods and food is high at all times and continues Over time, we all know the importance of products Maintaining the ﬂow of goods and cash and its role in the economy The problem is that despite the availability of goods and food, people do not have it easy access and often have to resort to traditional means to fnd a suitable one. The goal of this work is to create Plat models that organize the buying and selling process and help both the seller and Potential customers to interact better and fnd work (for merchants) and business means (customers) easily, and the result is a platform that allows customers to post their orders Merchants bid and customers can then choose the best deals that suit them , thus solving the above problem.